Intangible Investment and Changing Sources of Growth in Korea. (30th August 2015) - Chun, Hyunbae; Nadiri, M. Ishaq
Abstract : We examine how intangible investments change the sources of growth in the Korean economy. After constructing a novel industry‐level data set on intangibles, we estimate the contribution of intangible‐intensive industries and other industries to aggregate productivity growth in 1981–2008. The contribution of intangible‐intensive industries to aggregate labour productivity growth has significantly increased, whereas that of other industries has substantially decreased. The increased contribution of intangible‐intensive industries is mainly associated with total factor productivity growth rather than with input growth. This suggests that innovations related to intangible investments in these industries might become a new key source of productivity growth in Korea.